The genetics of obstructive sleep apnoea. Issue 1 (7th November 2017) - Mukherjee, Sutapa; Saxena, Richa; Palmer, Lyle J.
ABSTRACT: Obstructive sleep apnoea (OSA) is a common chronic disease and is associated with high social and economic costs. OSA is heritable, and there is evidence of both direct genetic contributions to OSA susceptibility and indirect contributions via 'intermediate' phenotypes such as obesity, craniofacial structure, neurological control of upper airway muscles and of sleep and circadian rhythm. Investigation of the genetics of OSA is an important research area and may lead to improved understanding of disease aetiology, pathogenesis, adverse health consequences and new preventive strategies and treatments. Genetic studies of OSA have lagged behind other chronic diseases; however recent gene discovery efforts have been successful in finding genetic loci contributing to OSA‐associated intermediate phenotypes. Nevertheless, many of the seminal questions relating to the genetic epidemiology of OSA and associated factors remain unanswered. This paper reviews the current state of knowledge of the genetics of OSA, with a focus on genomic approaches to understanding sleep apnoea.